A proposal for emotional intelligence development through dance movement therapy. Issue 2 (3rd April 2023) - Ortuño-Ibarra, Andrea; Rodríguez-Jiménez, Rosa-María
Abstract: Emotional Intelligence (EI) as a predictor of success has received a lot of attention since research shows that EI can be taught at any age. Traditionally emotional education has focussed on cognitive skills-based interventions. By connecting the principles of dance movement therapy (DMT), EI development, Emotional Regulation (ER) and the benefits of movement, a bridge is built permitting the proposal of a DMT EI Educational Model. Laban Bartenieff Movement Analysis (LBMA) together with the relationship between motor patterns and emotions is a core part of this proposal. A reflective process based on previous experiences of IE development in academic settings by one of the authors has enriched the model. It is organised into four modules; each module is associated with an EI branch, a social-emotional skill, a DMT element, an exploration quality, an aimed outcome and examples. Some suggestions about the applicability in different contexts and populations have also been incorporated.